Escherichia coli induces platelet aggregation in an FcγRIIa‐dependent manner. (19th February 2016) - Moriarty, R. D.; Cox, A.; McCall, M.; Smith, S. G. J.; Cox, D.
Abstract : Essentials Escherichia coli (Ecoli) ‐mediated sepsis is a serious illness associated with thrombocytopenia. Gram‐positive bacteria‐induced platelet activation has been characterized, but not Gram‐negative bacteria. E. coli induces platelet aggregation in an αIIb β3, FcγRIIa and donor‐dependent manner. E. coli is a potent inducer of platelet activation, and the Fc receptor is a possible drug target for sepsis. Summary: Background: The discovery of pathogen‐recognition receptors such as Toll‐like receptors on platelets has led to the emergence of the concept of platelets as important components of the host response to infection. Escherichia coli (E. coli) ‐mediated sepsis is a serious illness characterized by the occurrence of thrombocytopenia. Whereas there has been a wealth of research on platelet activation by Gram‐positive bacteria, little is known about the mechanisms associated with Gram‐negative bacteria‐induced platelet activation with Gram‐negative bacteria. Objectives: To determine the mechanisms by which Gram‐negative E. coli induces platelet aggregation. Methods: Induction of platelet aggregation with E. coli strain O157:H7 was tested in platelet‐rich plasma (PRP), washed platelets, and serum depleted of complement factors. Platelet inhibitors (against αII b β3, glycoprotein Ibα and FcγRIIa) were used. Platelet thromboxane synthesis was analyzed after E. coli stimulation. Cell binding assays were used to assess the ability of E. coli to support platelet adhesion. Trypsinization was used to determine the role of E. coli surface proteins. Results and conclusion: E. coli ‐induced aggregation in PRP was donor‐dependent. E. coli O157:H7 induced aggregation with a lag time of 6.9 ± 1.3 min in an αII b β3 ‐dependent and FcγRIIa‐dependent manner. Furthermore, this interaction was enhanced by the presence of complement, and was dependent on thromboxane synthesis. These results show E. coli to be a potent inducer of platelet aggregation.